Sposoby wzmocnienia aktu mowy dezaprobaty w języku polskim, rosyjskim i angielskim - Czapiga, Artur (Acta Polono-Ruthenica, 2019)
The present paper is devoted to the phenomenon of disapproval as a speech act in contrastive Polish-Russian-English perspective. Special attention is paid to the utterances in which the speaker strengthens the speech act. The material for the analysis was excerpted from contemporary literary works in the three above mentioned languages.Choosing to express negative evaluation and lack of consent, the sender acts against the rules of politeness – he/she does not agree with the receiver and even prevents the interlocutor from action. In certain circumstances the speaker decides to strengthen the disapproval in order to achieve a stronger effect on the listener. Such utterances usually contain extra elements like emotional lexemes, proverbs or rhetoric questions.